MYOFACIAL PAIN SYNDROME OF THE UPPER TRAPEZIUS MUSCLE INCIDENTS BASED ON AGE AND LENGTH OF WORK FOR BATIK TULIS WORKERS IN WIRADESA DISTRICT - Nurul Aktifah (Universitas Widya Husada Semarang, 2020)
Background: Myofascial pain syndrome of the upper trapezius muscle is pain in the muscles that is characterized by trigger points. Work with a statistical position for 8 hours every day can cause the syndrome. Objective: To determine the incidence of Myofascial pain syndrome of the upper trapezius muscle based on age and length of work of batik workers. Research Methods: Descriptive study. Respondents in this study were 25 batik workers using accidental sampling method. The research instrument uses the Visual Analogue Scale (VAS). Results: myofascial pain syndrome in upper trapezius muscle category of uncontrolled severe pain experienced by respondents aged 46-60 amounted to 10 respondents (40%) and the length of work less than 10 years were 11 respondents (44%). Conclusion: The results of this study illustrate that age and length of work can be risk factors for myofascial pain syndrome of upper trapezius muscle in batik tulis workers in Wiradesa District.